Corneal Collagen Cross-Linking With Riboflavin and Ultraviolet A Light for Pediatric Keratoconus: Ten-Year Results. Issue 5 (May 2018) - Mazzotta, Cosimo; Traversi, Claudio; Baiocchi, Stefano; Bagaglia, Simone; Caporossi, Orsola; Villano, Antonio; Caporossi, Aldo
Abstract : Purpose: To assess the 10-year follow-up efficacy and safety of riboflavin ultraviolet A–induced cross-linking (CXL) in a population of pediatric patients aged 18 years and younger with progressive keratoconus (KC). Methods: The prospective longitudinal cohort study included 62 eyes of 47 keratoconic patients undergoing epithelium-off CXL who completed 10-year follow-up. The surgical procedure was performed in all patients according to the Siena (Dresden modified) protocol. Evaluation included uncorrected distance visual acuity, corrected distance visual acuity, Scheimpflug corneal tomography, and optical coherence tomography demarcation line measurement. Follow-up measurements taken up to 10 years after treatment were compared with baseline values, and statistical analysis was performed using a 2-tailed paired sample Student t test. Results: Uncorrected distance visual acuity and corrected distance visual acuity improved from 0.45 to 0.23 logarithm of the minimum angle resolution ( P = 0.0001) and from 0.14 to 0.1 logarithm of the minimum angle resolution ( P = 0.019). KC stability was recorded after 10 years of follow-up in nearly 80% of the patients. The overall 10-year follow-up progression rate was 24% including 13 eyes of 9 patients with Kmax progression over 1 diopter and 2 eyes of 2 patients who underwent corneal grafting. Conclusions: The study demonstrates the ability of CXL to slow down KC progression in pediatric patients, improving functional performance. Long-term stability may be correlated with CXL-induced delay in corneal collagen turnover and with spontaneous age-related KC stabilization. A 24% regression rate could be contemplated in the patients who were aged 15 years and younger at the time of inclusion in the treatment protocol.